Exocytosis-related genes and response to methylphenidate treatment in adults with ADHD - da Silva, B S; Cupertino, R B; Rovaris, D L; Schuch, J B; Kappel, D B; Müller, D; Bandeira, C E; Victor, M M; Karam, R G; Mota, N R; Rohde, L A; Contini, V; et al. (Molecular psychiatry, 2018)
Experimental studies have demonstrated that methylphenidate (MPH) modulates the synaptic vesicle trafficking and synaptotagmin-1 (SytI) mRNA levels. SytI is a regulatory protein of the SNARE complex, a neurotransmitter exocytosis mediator. Despite this evidence, most SNARE complex-related genes have never been evaluated in attention-deficit/hyperactivity disorder (ADHD) pharmacogenetics. This study evaluates, for we believe the first time, polymorphisms on the SNARE complex-related genes STX1A (rs2228607), VAMP2 (26bp Ins/Del) and SYT1 (rs1880867 and rs2251214) on the response to immediate-release methylphenidate (IR-MPH) in a naturalistic sample of adults with ADHD. The sample comprised 433 subjects, of which 272 (62.8%) have completed the short-term IR-MPH treatment (at least 30 days). The main outcome measure was the categorical variable of short-term response to IR-MPH based on the Swanson, Nolan and Pelham Rating Scale version 4 (SNAP-IV), and on the clinical global impression-improvement scale. Additional analyses evaluated the percentage of SNAP-IV symptom reduction for each dimension as well as short- and long- (7 years) term treatment persistence. SYT1 -rs2251214 was associated with the categorical short-term response to IR-MPH ( P =0.006, P FDR =0.028), and with the percentage of inattention and oppositional defiant disorder symptoms reduction ( P =0.007, P FDR =0.028 and P =0.017, P FDR =0.048, respectively). SYT1 -rs2251214 was also associated with short-term treatment persistence ( P =0.018, P FDR =0.048), and with months of treatment ( P =0.002, P FDR =0.016) in the long-term protocol. Our findings suggest that SYT1 -rs2251214 presents a broad influence in IR-MPH response variability in adults with ADHD, being involved with both symptom response and treatment persistence. If such findings are replicated, SytI could represent a key element in MPH pharmacodynamics in adults with ADHD.